Ubuntu diplomacy: Broadening soft power in an African context. Issue 3 (4th March 2020) - Madise, Dikeledi; Isike, Christopher
Abstract : Ubuntu is an African philosophical worldview that has increasingly gained prominence since South Africa's democratic transition in 1994. It places emphasis on the world's common humanity and its consequent interdependence. Through content analysis, the article examines the soft power that is inherent in South Africa's foreign policy, as codified in the 2011 White Paper on South African Foreign Policy–Building a Better World: Diplomacy of Ubuntu . In its findings, the article established a distinction between Joseph Nye's original conceptualization of soft power, formulated from a United States realist foreign policy perspective, and the one inherent in South Africa's humanist foreign policy guided by the philosophy of Ubuntu. This distinction is premised on the geopolitical disparities between the two nations. The article further examines South Africa's wielding of soft power within the African continent, the first audience of the country's diplomacy of Ubuntu.